2019
DOI: 10.1159/000500569
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Cystoscopy and Vesicoamniotic Shunting in Lower Urinary Tract Obstruction: Long-Term Outcome and Current Technical Limitations

Abstract: <b><i>Background:</i></b> In utero therapeutic approaches for lower urinary tract obstruction (LUTO) have been developed to salvage the fetal kidney function. <b><i>Objective:</i></b> The aim of this work was to report the long-term survival, nephrological, and urological outcome of children treated prenatally for LUTO using operative fetal cystoscopy (FC) and vesicoamniotic shunting (VAS) or both. <b><i>Methods:</i></b> A retrospective st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 31 publications
0
22
0
7
Order By: Relevance
“…They noted that the candidates for fetal intervention could be appropriately selected based on fetoscopic findings. 25 In contrast, a retrospective study of 48 procedures (FC, n = 23; VAS, n = 25) reported by Vinit et al 26 showed that there were no significant differences in the long-term outcomes (including survival, the renal function, and urological outcomes) of the two groups. Inadequate visualization of the posterior urethra by FC was thought to have contributed to these results.…”
Section: Discussionmentioning
confidence: 91%
“…They noted that the candidates for fetal intervention could be appropriately selected based on fetoscopic findings. 25 In contrast, a retrospective study of 48 procedures (FC, n = 23; VAS, n = 25) reported by Vinit et al 26 showed that there were no significant differences in the long-term outcomes (including survival, the renal function, and urological outcomes) of the two groups. Inadequate visualization of the posterior urethra by FC was thought to have contributed to these results.…”
Section: Discussionmentioning
confidence: 91%
“…Fetal renal therapy options: • VAS is an ultrasound-guided procedure introducing a 1-way flow shunt/conduit between the obstructed fetal bladder and the amniotic cavity (Table 3, [15,[48][49][50][51][52][53]). • FC is ultrasound guided allowing direct vision of the urethralbladder floor with possible direct urethral-bladder floor therapy (Table 3, [15,[48][49][50][51][52][53]). • Fetal vesicostomy using open maternal-fetal or endoscopic approach with amnioinfusion (Table 3, [15,[48][49][50][51][52][53]).…”
Section: Results/interventions: Identification Of Potential Evidenced-based Protocol Elements For Development Of An Eras-luto Guidelinementioning
confidence: 99%
“…• FC is ultrasound guided allowing direct vision of the urethralbladder floor with possible direct urethral-bladder floor therapy (Table 3, [15,[48][49][50][51][52][53]). • Fetal vesicostomy using open maternal-fetal or endoscopic approach with amnioinfusion (Table 3, [15,[48][49][50][51][52][53]). • Amnioinfusion has been proposed for an improved ultrasound diagnostic opportunity with second trimester and/or oligohydramnios secondary to bladder neck obstruction and to allow fetal access for VAS or FC [54][55][56][57][58].…”
Section: Results/interventions: Identification Of Potential Evidenced-based Protocol Elements For Development Of An Eras-luto Guidelinementioning
confidence: 99%
See 1 more Smart Citation
“…Urological fistulas are usually caused by inadequate curvature of the instrument, fetal mobilization, and limited surgeon experience 147. The long term benefits of fetal cystoscopy over VAS remain undetermined and improvements of the instruments and techniques are warranted 149. Our group is currently investigating the benefits, safety, and risks related to fetal cystoscopy for stage II LUTO (ClinicalTrials.gov Identifier: NCT03281798).…”
Section: Fetal Endoscopic Surgeriesmentioning
confidence: 99%